Accelerated implementations of the RIME for DDE calibration and source modelling - Van Staden, Joshua (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2021)
Second- and third-generation calibration methods filter out subtle effects in interferometer data, and therefore yield significantly higher dynamic ranges. The basis of these calibration techniques relies on building a model of the sky and corrupting it with models of the effects acting on the sources. The sensitivities of modern instruments call for more elaborate models to capture the level of detail that is required to achieve accurate calibration. This thesis implements two types of models to be used in for second- and third-generation calibration. The first model implemented is shapelets, which can be used to model radio source morphologies directly in uv space. The second model implemented is Zernike polynomials, which can be used to represent the primary beam of the antenna. We implement these models in the CODEX-AFRICANUS package and provide a set of unit tests for each model. Additionally, we compare our implementations against other methods of representing these objects and instrumental effects, namely NIFTY-GRIDDER against shapelets and a FITS-interpolation method against the Zernike polynomials. We find that to achieve sufficient accuracy, our implementation of the shapelet model has a higher runtime to that of the NIFTY-GRIDDER. However, the NIFTY-GRIDDER cannot simulate a component-based sky model while the shapelet model can. Additionally, the shapelet model is fully parametric, which allows for integration into a parameterised solver. We find that, while having a smaller memory footprint, our Zernike model has a greater computational complexity than that of the FITS-interpolated method. However, we find that the Zernike implementation has floating-point accuracy in its modelling, while the FITS-interpolated model loses some accuracy through the discretisation of the beam.
Keywords: Radio astronomy; Radio inferometers; Radio inferometers -- Calibration; Radio astronomy -- Data processing; Radio inferometers -- Data processing; Radio inferometers -- Calibration -- Data processing